Screening for Stereopsis Using an Eye-Tracking Glasses-Free Display in Adults: A Pilot Study - Liu, Fang; Zhao, Jing; Han, Tian; Shen, Yang; Li, Meng; Liu, Jingrong; Yang, Dong; Fang, Yong; Yan, Li; Zhou, Xingtao (Frontiers in Medicine, 2022)
Purpose: To explore the feasibility and repeatability of a novel glasses-free display combined with random-dot stimulus and eye-tracking technology for screening stereopsis in adults. Methods: A total of 74 patients aged 18–44 years were recruited in this study (male: female, 32:42), including 33 patients with high myopia (≤ −6.0 diopters [D]) and 41 patients with moderate-to-low myopia (> −6.0 D). Stereopsis was measured using glasses-free, polarized, and Titmus stereotests. All patients completed a visual fatigue questionnaire after the polarized stereotest and glasses-free test. Kendall’s W and Cohen's Kappa tests were used to evaluate repeatability and consistency of the glasses-free stereotest. Results: The stereotest results using the glasses-free monitor showed strong repeatability in the three consecutive tests (W=0.968; P <0.01) and good consistency with the polarized stereotest and Titmus test results (vs. polarization: Kappa = 0.910, P <0.001; vs. Titmus: Kappa = 0.493, P <0.001). Stereopsis levels of the high myopia group were significantly poorer than those of the moderate-to-low myopia group in three stereotest monitors (all P <0.05). There was no significant difference in visual fatigue level between the polarized and the glasses-free display test (P =0.72). Compared with the polarized test, 56.76% of patients preferred the glasses-free display and found it more comfortable, 20.27% reported both tests to be acceptable. Conclusions: In our adult patients, the new eye-tracking glasses-free display system feasibly screened stereopsis with good repeatability, consistency, and patient acceptance.